Exploring the communication of flood risk through online geographic visualisation - Richardson, Emily (2021)
There is a growing need for effective flood risk communication in the UK, the Projection Augmented Relief Model (PARM) simulator is a unique, online geovisualisation tool that presents geographical information in a unique and engaging way. This research investigated the acquisition of geographical knowledge and the quality of user experience with a PARM simulator. The research explored how user-centred testing can be used to gain feedback and critical insights on the PARM simulator content, obtaining input from both technical and non-technical audiences. This was novel as there has been minimal formal testing of this kind on 3D PARMs, but the PARM content has also never been replicated online into a ‘simulator’ in this way. Without the replication of 3D content, this enabled the isolation of issues related directly to content rather than the display model. The methodology employed during this research included interviews where participant interactions with the simulator were observed and feedback was collected (Stage 1). Recommendations made by participants in Stage 1 were then implemented, modifying the PARM Simulator content. The PARM simulator was then made public, and a feedback survey was used to gain further insights into the successes and failures of the simulator (Stage 2). The overall findings highlighted that the local story of ‘What causes Skipton to flood?’ was deemed, on average, the most engaging thematic section. The catchment-scale imagery and explanations used here should be replicated for future displays that aim to convey flood risk. The ‘Scenario Animations’ were statistically proven to be rated, on average, significantly more engaging by those who were familiar with Skipton compared to those who were not. Yet, familiarity of location did not provide users with a significant advantage in knowledge acquisition from the simulator overall, meaning that the PARM narrative was more accessible than previously expected. Graphic representation of different flood events (% AEP) was the most useful in helping users understand flood risk in Skipton, however future deigns should incorporate ‘return period’ language into the PARM narrative and an explanation of language used, especially for stand-alone displays. This research presents a list of feedback from both stages of investigation to be considered when designing and creating content for PARM displays in the future. The PARM simulator was proven to evoke behavioural change amongst users, who signed up to a flood warning scheme as a result of engaging with the simulator. Future work should consider how PARM displays can inform users on private flood risk reduction behaviours. It was also found that alternative online platforms for the simulator should be explored, such as websites, to produce a more intuitive risk communication tool that could be disseminated further to engage non-technical audiences.